The Impact of Feeding Rates on the Growth, Stress Response, Antioxidant Capacity, and Immune Defense of Koi (Cyprinus carpio var. koi) - Saixing Duan; Shengyu Gao; Xiaolong Xu; Qi Wei; Ze Tao; Gaoxiao Xu; Quanzhou Liu; Bing Wei; Chaofan He (Fishes, 2025)
The feeding rate is critical for fish growth and the feed conversion ratio (FCR). Prior research has primarily evaluated the optimal feeding rate by examining growth performance and the FCR. Given the high cost of koi as an ornamental fish, it is essential to consider the effects of feeding rates on its welfare and health. This study aimed to examine the impact of the feeding rate on the growth, stress response, antioxidant capacity, and immune defense of koi. A total of 240 fish, with an initial body weight of 10.02 ± 0.18 g, were randomly assigned to six groups and fed expanded diets at 1%, 2%, 3%, 4%, 5%, and 6% of body weight per day (BW/day) for a duration of eight weeks. The study results indicated that the daily weight gain of fish at 3–4% BW/day was significantly greater than that of the other groups. Fish in both high and low feeding rate groups exhibited reduced antioxidant capacity and heightened inflammatory response, as indicated by a notable decrease in catalase (CAT) and superoxide dismutase (SOD) activity, along with diminished expression of cat and sod, as well as a significant increase in the expression of tnf-α, il1, and il10. The elevated feeding rate did not enhance immune defense mechanisms. Furthermore, a low feeding rate resulted in heightened stress and reduced immunity in koi, as indicated by a significant reduction in plasma cortisol (COR), complement C3, complement C4, total protein (TP), albumin (ALB), and globulin (GLO) levels, along with decreased activities of lysozyme (LZM) and myeloperoxidase (MPO). The optimal feeding rate for enhancing non-specific immunity in koi is a daily intake of 3–4% of body weight on extruded feed. Our findings reveal that underfeeding led to diminished antioxidants and immune defenses in koi, while overfeeding also proved detrimental. An optimal feeding rate of 3–4% body weight per day is necessary to enhance growth and health in this species.